PTEN hamartoma tumor syndrome in childhood and adolescence-a comprehensive review and presentation of the German pediatric guideline. - Plamper, Michaela; Gohlke, Bettina; Wölfle, Joachim (Molecular and Cellular Pediatrics, 2022)
BACKGROUND: The PTEN hamartoma tumor syndrome (PHTS) encompasses several different syndromes, which are linked to an autosomal-dominant mutation of the tumor suppressor PTEN gene on chromosome 10. Loss of PTEN activity leads to an increased phosphorylation of different cell proteins, which may have an influence on growth, migration, and apoptosis. Excessive activity of the PI3K/AKT/mTOR pathway due to PTEN deficiency may lead to the development of benign and malignant tumors and overgrowth. Diagnosis of PHTS in childhood can be even more challenging than in adulthood because of a lack of well-defined diagnostic criteria. So far, there are no official recommendations for cancer surveillance in affected children and adolescents. MAIN BODY: All individuals with PHTS are at high risk for tumor development and thus might benefit from cancer surveillance strategies. In childhood, macrocephaly may be the only evident symptom, but developmental delay, behavioral problems, dermatological features (e.g., penile freckling), vascular anomalies, lipoma, or enlarged perivascular spaces in cerebral magnetic resonance imaging (cMRI) may help to establish the diagnosis. Regular psychomotor assessment and assistance in subjects with neurological impairment play an important role in the management of affected children. Already in early childhood, affected patients bear a high risk to develop thyroid pathologies. For that reason, monitoring of thyroid morphology and function should be established right after diagnosis. We present a detailed description of affected organ systems, tools for initiation of molecular diagnostic and screening recommendations for patients < 18 years of age. CONCLUSION: Affected families frequently experience a long way until the correct diagnosis for their child's peculiarity is made. Even after diagnosis, it is not easy to find a physician who is familiar with this rare group of diseases. Because of a still-limited database, it is not easy to establish evidence-based (cancer) surveillance recommendations. The presented screening recommendation should thus be revised regularly according to the current state of knowledge.
EVALuna2:519679